RESEARCH NOTES. NETWORKS WITHIN NETWORKS: SERVICE LINK OVERLAP, ORGANIZATIONAL CLIQUES, AND NETWORK EFFECTIVENESS. - Provan, K. G.; Sebastian, J. G. (Academy of Management Journal, 1998)
This study explored the use of clique analysis for explaining network effectiveness. In data from networks of mental health agencies in three cities, effectiveness, measured as client outcomes, was...